2019
DOI: 10.1002/bit.27195
|View full text |Cite
|
Sign up to set email alerts
|

Survival of aging CD264+ and CD264 populations of human bone marrow mesenchymal stem cells is independent of colony‐forming efficiency

Abstract: In vivo mesenchymal stem cell (MSC) survival is relevant to therapeutic applications requiring engraftment and potentially to nonengraftment applications as well. MSCs are a mixture of progenitors at different stages of cellular aging, but the contribution of this heterogeneity to the survival of MSC implants is unknown. Here, we employ a biomarker of cellular aging, the decoy TRAIL receptor CD264, to compare the survival kinetics of two cell populations in human bone marrow MSC (hBM‐MSC) cultures. Sorted CD26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…CFU, colony-forming unit; hBMSCs, human bone marrow mesenchymal stem cells; Luc, luciferase CD264 + cells (Fig. 1b) [4]. These findings cast doubt on the utility of colony-forming efficiency as a metric of in vivo survival.…”
Section: In Vitro and In Vivo Survivalmentioning
confidence: 99%
See 3 more Smart Citations
“…CFU, colony-forming unit; hBMSCs, human bone marrow mesenchymal stem cells; Luc, luciferase CD264 + cells (Fig. 1b) [4]. These findings cast doubt on the utility of colony-forming efficiency as a metric of in vivo survival.…”
Section: In Vitro and In Vivo Survivalmentioning
confidence: 99%
“…Our findings do not support this supposition. In the study described above, we compared the survival of CD264 +/− hBMSCs attached to ceramic scaffolds, which were implanted subcutaneously in immunodeficient mice [4]. Bioluminescence imaging revealed that matched implants of CD264 − and CD264 + hBMSCs from the same culture had a similar in vivo half-life despite a lower colony-forming efficiency for the aging Fig. Illustration of the discrepancy between the colony-forming efficiency and survival of CD264 +/− populations of hBMSCs.…”
Section: In Vitro and In Vivo Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, low but not high CD146 expression was associated with a senescent phenotype in MSCs (Jin et al, 2016), and CD146 + MSCs showed increased migratory potential toward degenerating tissues (Wangler et al, 2019). CD264 is another surface marker of in vitro aging in MSCs that is unrelated to the chronologic age of the donor (Madsen et al, 2017); cells expressing this protein exhibit increased senescence-associated β-galactosidase (SA-β-gal) activity and reduced differentiation potential and colony-forming efficiency compared to CD264 − MSCs (Madsen et al, 2020). Other surface markers that show altered expression with in vitro/in vivo aging are summarized in Table 2.…”
Section: Phenotypic Heterogeneity Of Senescent Mscsmentioning
confidence: 99%